FAKTOR – FAKTOR YANG BERHUBUNGAN DENGAN UPAYA WANITA USIA SUBUR MELAKUKAN DETEKSI DINI KANKER SERVIKS - Yuhani Diasih; Reni Zulfitri; Rismadefi Woferst (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2018)
Women of reproductive age (WRA) are women in the childbearing period which is around 15 - 49 years old. Women of reproductive age are a vulnerable age to get health problems one of them is cervical cancer. This study aimed to determine the factors associated with the efforts of women of reproductive age performing early detection of cervical cancer at the supported area of Puskesmas Harapan Raya. The design of the research was descriptive correlational research with cross-sectional approach. The sample was 100 respondents taken by using purposive random sampling technique. The sample of the study showed that the majority of respondents were at the age of 35-45 years old (42%), the high school education levels were 54% and working as housewives were (73%). Based on the results of statistical tests, it found the data of knowledge variable p value <alpha (0,000 <0.05) which means there is a relationship, on the family support variable obtained data (0.004 <0.05) which also means there is a relationship, on the availability of facilities variable obtained results (0.001 <0,05) which means there is relationship and attitude variable got result (0,000 <0,05) which mean there is relationship between attitude and effort of women of reproductive age conducting early detection of cervical cancer. The research findings recommend that health workers maximize the health care services to provide facilities as well as providing information for early detection of cervical cancer and increase family support that affects the attitude of women of reproductive age.Keyword : Cervical cancer, early detection, women of reproductive age